2007
DOI: 10.1111/j.1523-1739.2007.00761.x
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of the Southern Patagonia Ocean by Exotic Chinook Salmon

Abstract: Anadromous salmonids have been particularly successful at establishing wild populations in southern Patagonia, in contrast to their limited success elsewhere outside their native ranges. The most recent such discovery is a spawning population of Chinook salmon in the Santa Cruz River, which flows into the Atlantic Ocean from Argentina. We used mitochondrial DNA analysis to discriminate between alternative potential sources of this population and were able to discard in situ introductions of fish imported direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 25 publications
2
63
0
1
Order By: Relevance
“…Similar flash expansions due to high straying have been documented in populations introduced at low density in Patagonia (Becker et al 2007;Correa and Gross 2008) and the Great Lakes (Emery 1981;Kwain and Lawrie 1981).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Similar flash expansions due to high straying have been documented in populations introduced at low density in Patagonia (Becker et al 2007;Correa and Gross 2008) and the Great Lakes (Emery 1981;Kwain and Lawrie 1981).…”
Section: Introductionmentioning
confidence: 75%
“…While possible, Allee effects in salmon populations are rarely observed (Liermann and Hilborn 1997). At a larger scale, reduced homing at low density should facilitate coloniza tion (Ayson 1921;Emery 1981;Kwain and Law rie 1981;Becker et al 2007;Correa and Gross 2008), which is profoundly important for salmon because colonization (post glacial, including the present time in Alaska) has been a dominant pro cess in salmon ecology. Across multiple scales, sal monids are locally adapted (Taylor 1991;Fraser et al 2011;Westley et al 2012) and there is much interpopulation genetic heterogeneity.…”
Section: Ecological and Evolutionary Implicationsmentioning
confidence: 99%
“…Hughes et al (2003) showed that a resident genotype of freshwater shrimp was extinct after translocation of slightly different genotypes. Sometimes hybrids result from intended release programs (Becker et al 2007), and in other cases from habitat alterations (Freyhof et al 2005) or from unintended escapes of hatchery fish (Birstein et al 1998). However, natural sturgeon hybrids are often rare (Ludwig et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the geographic arrangement of colonizing species can provide very useful information for the first issue, while setting the stage for studies on the second issue. The present distribution of Chinook salmon in Patagonia is very extensive (Soto et al 2006, Becker et al 2007, Correa & Gross 2007, from 39 o S on the Pacific, all the way south to the Strait of Magellan and to the Santa Cruz River on the Atlantic Ocean. The colonization of Patagonian rivers by Chinook salmon provides such an opportunity to explore invasion and ecological responses in real time.…”
Section: Discussionmentioning
confidence: 99%
“…As salmon aquaculture increased, so did reports of fish straying into rivers of southern Chile (Soto et al 2001) and Argentina (Grosman 1992, Ciancio et al 2005, Becker et al 2007, Pascual & Ciancio 2007. Because of the complexity of the salmon life cycle, their introgression can have cascading effects on both marine and freshwater communities (Pascual & Ciancio 2007).…”
Section: Introductionmentioning
confidence: 99%